Therapeutic use of tetrasodium ethylenediaminetetraacetic acid solution for treatment of subcutaneous ureteral bypass device mineralization in cats. (6th August 2019) - Chik, Colin; Berent, Allyson C.; Weisse, Chick W.; Ryder, Marcia
Abstract: Background: Subcutaneous ureteral bypass (SUB) device placement is an increasingly popular treatment option for decompression of ureteral obstruction in cats. Mineralization occlusion of the device occurs in a minority of cases but is the most common complication. Objective: To evaluate a 2% tetrasodium ethylenediaminetetraacetic acid (tEDTA) solution for treatment of mineralization occlusion in cats with SUBs. Animals: Six client‐owned cats (8 obstructed devices). Methods: Case series. Each cat was found to have device occlusion based on a combination of ultrasound examination, SUB irrigation, and failure to identify another cause of device obstruction. Each SUB was drained, irrigated using sterile saline, and infused with 1‐2 mL of 2% tEDTA solution. Success was defined as normalization of flow during subsequent ultrasound visualization while irrigating. The volume and frequency of tEDTA instillations, time to achieve device patency, follow‐up biochemical and ultrasound findings, and future reobstruction events were recorded. Results: Resolution of mineralization was documented in all 8 SUBs. Reobstruction events occurred in 2 cats, all of which resolved after additional tEDTA infusions, but 1 cat ultimately required device exchange at 356 days from the first tEDTA infusion. In 1 cat, a single infusion was prematurely discontinued because of persistent pelvic dilatation after 1.25 mL of tEDTA had been instilled. No complications were observed. Conclusions and Clinical Importance: Tetrasodium EDTA infusions can be safely considered as a treatment option for mineralized SUB devices in cats. This solution was easily infused, well tolerated, and avoided the need for SUB device exchange in the majority of cats in which it was used.